Biocatalysis enables the scalable conversion of biobased furans into various furfurylamines - Giri, Pritam; Lim, Seonga; Khobragade, Taresh P.; Pagar, Amol D.; Patil, Mahesh D.; Sarak, Sharad; Jeon, Hyunwoo; Joo, Sangwoo; Goh, Younghwan; Jung, Seohee; Jang, Yu-Jeong; Choi, Seung Beom; et al. (NATURE COMMUNICATIONS, 2024)
Keywords: Biomass; OMEGA-TRANSAMINASE; OXIDASE; Reductive amination; SPECIFICITY

photoarchitectonic hydrogel for synergistic in vitro chemo–phototherapy of breast cancer - Paul, Shatabdi; Yadav, Binduma; Patil, Mahesh D.; Pujari, Anil Kumar; Singh, Umesh; Rishi, Vikas; Bhaumik, Jayeeta (Materials Advances, 2024)
Currently, combinatorial therapy has evoked interest in cancer treatment, and may promote achieving a synergistic effect using cancer medicines. Laser-assisted and pH-responsive therapies have attracted significant attention, and their combination leads to high efficiency cancer treatment. Herein, we developed a chemo–phototherapeutic hydrogel comprised of doxorubicin (DOX, a chemotherapeutic drug) and zinc phthalocyanine (ZnPc, a phototherapeutic drug) for combinatorial and synergistic treatment of breast cancer. Firstly, we have developed carbon dots (CDs, size of ∼5 nm) utilizing lignin and folic acid as biocompatible sources. Then doxorubicin was loaded on the surface of the carbon dots via conjugation (DOX@CDs). Later on, zinc phthalocyanine and acrylic acid derivatives were utilized to develop a laser-responsive hydrogel (ZnPc-PP H). Afterward, doxorubicin-conjugated carbon dots were incorporated into the photoarchitectonic hydrogel to develop a chemo–phototherapeutic drug-loaded hydrogel (DOX@CDs–ZnPc-PP H). Subsequently, the in vitro pH-triggering experiments demonstrated that the hydrogel loaded with both DOX and ZnPc could release the drugs in an acidic environment. Interestingly, in vitro assays confirmed that DOX@CDs–ZnPc-PP H could effectively target breast cancer cells (MCF-7). Furthermore, the developed chemo–phototherapeutic hydrogel exhibited non-cytotoxic behavior. Owing to laser assisted reactive oxygen species generation from ZnPc present in the hydrogel, the growth of MCF-7 cells was significantly lowered. In conclusion, all experimental outcomes indicate that the photoarchitectonic hydrogel has the potential to be applied in synergistic chemo- and photodynamic therapy of cancer.

Immobilization of aldehyde reductase for the production of bioplastic precursors from agricultural fatty acids - Mohne, Devesh; Reddy, Yeddula Nikhileshwar; Rawat, Kshitij; Patil, Mahesh D.; Bhaumik, Jayeeta (RSC Sustainability, 2025)
<div class="abstract author" id="aep-abstract-id6" style="box-sizing: border-box; margin: 0px 0px 8px; padding: 0px; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;"> Herein, we report the biosynthesis of bioplastic precursors thourgh the immobilization of aldehyde reductase (AHR) onto a metal organic framework (UIO-66-NH2). Kinetic analysis demonstrated that the immobilized AHR maintained significant catalytic activity and exhibited improved operational stability, as well as higher reusability, compared with the free AHR. Furthermore, the synthetic applicability of the immobilized AHR was evaluated in tandem with that of transaminase derived from S. pomeroyi (spTA), where 8, 10, and 12 carbon chain ω-amino fatty acids (ω-AFAs) were biosynthesized from the corresponding hydroxy fatty acids (ω-HFAs) with ∼90% conversions. <div class="abstract graphical" id="aep-abstract-id8" style="box-sizing: border-box; margin: 0px 0px 8px; padding: 0px; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;"> Herein, we report the biosynthesis of bioplastic precursors via the immobilization of aldehyde reductase (AHR) onto a metal organic framework (UIO-66-NH2).

Total biocatalytic synthesis of capsaicinoids using ferulic acid: a versatile two-step strategy for natural product diversification - Khobragade, Taresh P.; Giri, Pritam; Patil, Mahesh D.; Joo, Sangwoo; Cho, Sunga; Kim, Yechan; Ghosh, Rohan; Jeong, Sanghun; Maeng, Minyeong; Song, Min-Ho; Park, Jeong-Min; Lee, Eun Ho; et al. (Angewandte Chemie-International Edition, 2025)
The wide-ranging application of capsaicinoids, the active compounds in chili peppers, has driven increasing interest in the development of sustainable production strategies. However, capsaicinoid synthesis remains a challenge. The objective of this pioneering study is to report the total biocatalytic synthesis of structurally diverse capsaicinoids from bio-based ferulic acids. An X-ray crystallographic study elucidated the structural basis for the exceptional potential of a novel transaminase from Phaeobacter porticola (PPTA) to transform the highest ever reported concentration of vanillin (100-200 mM) to vanillylamine, with >99% conversion and modest conversion ranging from 48% to 79% for 300 to 500 mM substrate. Using PPTA in tandem with phenolic acid decarboxylase (PAD) and aromatic dioxygenase (ADO) further enabled the direct synthesis of vanillylamine from ferulic acid with >99% conversion. Furthermore, the integration of a multi-enzymatic cascade with carboxylic acid reductases (CARs) successfully synthesized structurally diverse capsaicinoids via amide bond formation between vanillylamine and free fatty acids, with excellent conversions ranging from 72% to >88%. A 50-mM enzymatic reaction afforded 95% and 80% conversion of vanillylamine and capsaicin, respectively.
Keywords: Capsaicinoids; Carboxylic acid reductase; Transaminase; Vanillylamine